2009
DOI: 10.1007/s11869-009-0040-4
|View full text |Cite
|
Sign up to set email alerts
|

Determination of nitrogen dioxide, sulfur dioxide, ozone, and ammonia in ambient air using the passive sampling method associated with ion chromatographic and potentiometric analyses

Abstract: Concentrations of nitrogen dioxide (NO 2 ), sulfur dioxide (SO 2 ), ozone (O 3 ), and ammonia (NH 3 ) were determined in the ambient air of Al-Ain city over a year using the passive sampling method associated with ion chromatographic and potentiometric detections. IVL samplers were used for collecting nitrogen and sulfur dioxides whereas Ogawa samplers were used for collecting ozone and ammonia. Five sites representing the industrial, traffic, commercial, residential, and background regions of the city were mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 52 publications
2
30
2
1
Order By: Relevance
“…This concentration in Abidjan is comparable to those measured in Bamako (16.2 ppb) and Shenzhen (20.7 ppb) reported by Adon et al (2016) and Xia et al (2017). However, it remains lower than the concentrations obtained in Dakar (31.7 ppb) and Al Ain in the Middle East (31.5 ppb) and reported respectively by Adon et al (2016) and Salem et al (2009). The average concentration of NH 3 measured at the Abidjan traffic site (27.2 ppb) in this study is higher than those obtained in Dakar (21.1 ppb), Al Ain (17.1 ppb) and St John's (9.5 ppb), respectively reported by Adon et al (2016), Salem et al (2009) and Kumar et al (2004).…”
Section: Traffic and Urban Sitessupporting
confidence: 80%
See 2 more Smart Citations
“…This concentration in Abidjan is comparable to those measured in Bamako (16.2 ppb) and Shenzhen (20.7 ppb) reported by Adon et al (2016) and Xia et al (2017). However, it remains lower than the concentrations obtained in Dakar (31.7 ppb) and Al Ain in the Middle East (31.5 ppb) and reported respectively by Adon et al (2016) and Salem et al (2009). The average concentration of NH 3 measured at the Abidjan traffic site (27.2 ppb) in this study is higher than those obtained in Dakar (21.1 ppb), Al Ain (17.1 ppb) and St John's (9.5 ppb), respectively reported by Adon et al (2016), Salem et al (2009) and Kumar et al (2004).…”
Section: Traffic and Urban Sitessupporting
confidence: 80%
“…However, it remains lower than the concentrations obtained in Dakar (31.7 ppb) and Al Ain in the Middle East (31.5 ppb) and reported respectively by Adon et al (2016) and Salem et al (2009). The average concentration of NH 3 measured at the Abidjan traffic site (27.2 ppb) in this study is higher than those obtained in Dakar (21.1 ppb), Al Ain (17.1 ppb) and St John's (9.5 ppb), respectively reported by Adon et al (2016), Salem et al (2009) and Kumar et al (2004). Adon et al (2016) also reported a concentration of NH 3 in Bamako (46.7 ppb) 2 times higher than that obtained in Abidjan.…”
Section: Traffic and Urban Sitescontrasting
confidence: 67%
See 1 more Smart Citation
“…Majority of the studies reviewed revealed results comparable to outdoor NO 2 concentrations measured at Putra-Makhota and Kajang Toll Plaza, with low and medium traffic densities respectively. For example, NO 2 concentrations in a high traffic area in Abu Dhabi varied from 0.023 to 0.043 [53], while da Silva et al [21], reported NO 2 concentrations ranging between 0.031 -0.036 in Brazil, which are within the range of NO 2 concentrations measured at Putra Makhota Toll Plaza. High traffic density highway NO 2 concentration in Texas [54] was found to be lower than those reported in this study, as well as Salem et al [53] and da Silva [21].…”
Section: T Ekeu-wei Et Almentioning
confidence: 74%
“…Their disadvantages are low sensitivity, inability to resolve short duration 15 concentration peaks, and adverse effects of meteorological conditions on reported observations (Tang et al 1997(Tang et al , 1999Krupa and Legge, 2000;Tang, 2001;Kirby et al, 2001;Partyka et al, 2007;Fraczek et al, 2009;Salem et al, 2009;Zabiegala et al, 2010). Moreover, the passive monitors depend on monthly meteorological information, needed in order to calculate diffusion rates.…”
Section: Monitoring Datamentioning
confidence: 99%